FISHING PRODUCTIVITY OF SCADS RELATED TO SEA SURFACE TEMPERATURE AND CHLOROPHYLL-A IN CENTRAL JAVA WATERS: PRODUKTIVITAS PERIKANAN IKAN LAYANG TERKAIT SUHU PERMUKAAN LAUT DAN KLOROFIL-A DI PERAIRAN JAWA TENGAH - Iya Purnama Sari; Rakhma Fitria Larasati; I Made Satria Maulana Wibowo (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2026)
Intensive exploitation of small pelagic resources in Central Java threatens long-term sustainability. This study aims to investigate fishing productivity of scads related to sea surface temperature and chlorophyll-a at Bajomulyo Fishing Port to provide an evidence-based foundation for sustainable management. Fishing productivity is expressed as catch weight per setting, focusing on two main species, i.e., shortfin scads - SS (Decapterus macrosoma) and Indian scads - IS (Decapterus russelli). Research was carried out from December 2022 to March 2023 to collect catch data of the fishing boat. Onboard observations were carried out to obtain data of scads, the catch (in kg) and effort data (number of settings) were collected monthly. Monthly fishing productivity was calculated as catch per unit effort (CPUE), and its relationships with environmental variables, namely chlorophyll-a concentration and sea surface temperature (SST), were analyzed using regression analysis. The highest CPUE was recorded in October 2022 (i.e. 1,054 kg/setting for SS and 1,081 kg/setting for IS), while the lowest was in January 2023 (189 kg/setting) and February 2023 (242 kg/setting), respectively. The CPUE and the fishing effort do not show linear relationships: CPUE = -16.36f + 829.62 (R² = 0.2610 for SS), and CPUE = -12.143f + 706.79 (R² = 0.1555 for IS). Seasonal fluctuations in CPUE were closely associated with changes in environmental conditions, i.e. high CPUE corresponds with high concentration of chlorophyll-a and low SST.